Mechanical properties of isotactic 1-butene-ethylene copolymers from Ziegler-Natta catalyst. (22nd February 2021) - Ruiz de Ballesteros, Odda; Auriemma, Finizia; Di Girolamo, Rocco; Malafronte, Anna; Scoti, Miriam; De Rosa, Claudio
Abstract: The mechanical properties and elastic behavior of Ziegler-Natta isotactic 1-butene-ethylene (BuEt-ZN) copolymers, having a broad composition from 1.7 to 45.5 mol% of ethylene units, are studied. The multi-site nature of the catalytic system determines a non-uniform distribution of the comonomers along the polymer chains; the copolymers present a blocky microstructure and composed of fractions of chains made of long and short butene sequences, which can be separated by solvent fractionation procedures. Incorporation of ethylene induces improving of drawability and decrease of rigidity with respect to homopolymer, associated with the lower crystallinity, and outstanding elastomeric behavior when the ethylene amount exceeds 5.5 mol%. In these copolymers the presence of irregular fractions of chains with short butene sequences, showing crystallization of the defective and low-melting temperature form I′ upon aging of the amorphous at room temperature, is responsible for the good elasticity of the materials. Graphical abstract: Image 1 Higlights: The mechanical behavior of BuEt-ZN blocky copolymers is studied. The BuEt-ZN copolymers show remarkable elastomeric properties. The formation of form I′ by crystallization of amorphous is the key for the elasticity.